Faktor yang Paling Dominan Mempengaruhi Rendahnya Motivasi Belajar Mahasiswa Prodi Pendidikan Matematika - Melinda Rismawati (EDUPEDIA, 2021)
This study aims to determine what factors have the most dominant influence on the low motivation to learn mathematics subjects related to algebra, geometry, calculus, statistics, and trigonometry in students of the Mathematics education program STKIP Persada Khatulistiwa Sintang. This study uses a quantitative approach with data analysis using exploratory factor analysis and descriptive analysis with 64 research subjects as students of the Mathematics Education Study Program of STKIP Persada Khatulistiwa. The results showed that the most dominant factor affecting the low learning outcomes of mathematics education study program students was the learning facilities factor with a variance percentage of 20.914%. Keywords: The most dominant factor, learning motivation